Proactive maintenance control program for mechanical equipment used in the transport of hydrocarbons in Ecuador - Sergio Núñez, Solano; Moscoso Jácome, Ronal; Rivas Tufiño, Eduardo (mktDESCUBRE; Vol 1 No 14 (2019): Fourteenth Edition (July - December), 2019)
This research is based on concepts of maintenance in recent years, epistemologically speaking industrial maintenance is the set of preventives, predictive or corrective tasks in order to have a machine or a system of machines in optimal conditions for operation at lower cost. The objective of the study was to determine the relationship between corrective maintenance and proactive maintenance of mechanical equipment for hydrocarbon transport in Ecuador. A new maintenance theory called proactive is defined which is executed by a computer system, which in reality is a software that uses algorithms for the concatenation between both corrective, preventive and predictive maintenance joining them in a single program, resulting in a optimization of maintenance in mechanical systems of hydrocarbon transport. The methodology used is quantitative approach; The type of applied research is documentary and experimental, the observation in situ provided information as the first source. The most important results are the improvement in failure stops, cost reduction, savings, maintenance optimization in mechanical systems of hydrocarbon transport that have given sustainable development to the company and the country.